2021
DOI: 10.21203/rs.3.rs-151189/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal Variation of Biosynthetic Path Selectivity of Flavonoids, and Content and Antioxidant Activity of Metabolites in Tetrastigma Hemsleyanum Diels Et Gilg

Abstract: This work investigated the seasonal variations in biosynthetic path selectivity of nine individual flavonoids, and content and antioxidant activity of three major metabolites in Tetrastigma hemsleyanum. The results revealed that under conditions of precipitation (2.0~6.6 mm), temperature (17.5~24.1°C), humidity (67.3~80.2%) and sunshine duration (3.4~5.8 h) in April and May, the total content of flavonoids reached higher levels between 282 and 394.5 μg/g; in the second half of April with the highest accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…A total of 21 flavonoids were detected in the L of T. hemsleyanum , and 15 flavonoids were detected in the R ( Figure 1E ). Shi et al (2022) observed that the flavonoids in T. hemsleyanum were affected by external environment, similar to our results. We employed UV treatments to regulate the flavonoids of T. hemsleyanum (naringenin, astragaline, kaempferol, isorhamnetin, diosmetin-7G, isorhamnetin-3G, apigenin-7G, baicalin, apigenin, quercitrin, luteolin, eriodictyol, myricetin, diosmetin, lonicerin, rutin, orientin, vitexin, naringin, isoquercitrin, chrysoeriol, luteoloside, and hesperidin) and increased the flavonoid contents and varieties to further improve the quality of T. hemsleyanum ( Figure 1E ).…”
Section: Resultssupporting
confidence: 92%
“…A total of 21 flavonoids were detected in the L of T. hemsleyanum , and 15 flavonoids were detected in the R ( Figure 1E ). Shi et al (2022) observed that the flavonoids in T. hemsleyanum were affected by external environment, similar to our results. We employed UV treatments to regulate the flavonoids of T. hemsleyanum (naringenin, astragaline, kaempferol, isorhamnetin, diosmetin-7G, isorhamnetin-3G, apigenin-7G, baicalin, apigenin, quercitrin, luteolin, eriodictyol, myricetin, diosmetin, lonicerin, rutin, orientin, vitexin, naringin, isoquercitrin, chrysoeriol, luteoloside, and hesperidin) and increased the flavonoid contents and varieties to further improve the quality of T. hemsleyanum ( Figure 1E ).…”
Section: Resultssupporting
confidence: 92%
“…Studies have revealed that extracts prepared from the same plant species but collected at different times of the year and/or different locations can present significant differences in their chemical profiles, which in turn affects biological activity (Bibi et al, 2022;Reyes-Vaquero et al, 2021;Shi et al, 2022). The could be due to the presence of defensive compounds targeting these enzymes in insects (Ryan & Byrne, 1988).…”
Section: Ta B L Ementioning
confidence: 99%